Peranan Keagenan Dalam Penyediaan Fresh Water Di Atas Kapal MV. Serasi V pada PT. Admiral Lines Cabang Belawan - Sabila, Fadiyah Hani; Hidayat, Syarif (Politeknik Bumi Akpelni, 2025)
Admiral Lines Belawan Branch is a ship agency services company that acts as a representative for ship owners/principals in managing ship documents at the port for arrivals and departures. As a terminal for ships and cargo, the port requires adequate facilities and services to ensure smooth and efficient operations, supported by the Inaport-net system to facilitate administrative processes. As a ship agent, PT. Admiral Lines plays a crucial role in providing fresh water with various strategic functions. The company coordinates with clean water service providers to ensure quality according to international health and safety organization standards. The process includes ordering from trusted providers, arranging timely delivery logistics, monitoring water quality, managing efficient operational costs, and maintaining active communication with the crew to meet clean water needs. The Phinnisi system is utilized to support the efficiency and smoothness of managing fresh water provision on board. Through this comprehensive approach, PT. Admiral Lines can ensure the provision of safe and high-quality clean water, enhance customer satisfaction, and guarantee smooth ship operations. This research employs field research and library research methodologies to analyze the company's roles and functions within the shipping industry.